Pemberdayaan Masyarakat Melalui Peningkatan Pemasaran Pada Usaha Kerupuk “Damai” Dusun Bonggan Kel. Blotongan Kota Salatiga - Pandi Afandi; Aan Istiyanto; Dina Ayu Lestari; Mada Adi Wibowo (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
SMEs or home traders are another term or term for productive economic businesses owned by individuals or business entities. MSMEs or home traders usually earn income that can be said to be the least compared to entrepreneurs in the medium and large categories. This is due to the small scope of sales and a lack of sales facilities and even the required capital. This implementation is supported by the Community Empowerment Practice Lecture (KPPM) organized by LP2M and STIE